Supporting Moral and Religious Development in Early Childhood Through a Scientific Approach: Evidence from an Indonesian Kindergarten - Putri, Suci Utami; Jayadinata, Asep Kurnia; Putri, Aries Legita Permana; Yuliyanto, Aan (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Moral and religious development in early childhood remains a significant pedagogical concern, particularly in classroom settings where values are often introduced through routine instruction rather than through active meaning-making. This study examined whether a scientific approach could support children’s moral and religious development in an early childhood classroom in Indonesia. A quantitative pre-experimental design with a one-group pre-test post-test format was employed in Group B1 at Tunas Harapan Kindergarten, Purwakarta. The analytic sample consisted of 24 children aged 5 to 6 years. Data were collected through an observation sheet covering five indicators: mentioning important religious days, demonstrating polite behavior, identifying places of worship and religion, demonstrating patience, and respecting peers in ways consistent with religious teachings. The data were analyzed using descriptive statistics, N-gain analysis, and a paired-samples t-test. The findings showed an increase in the mean score from 12.62 at pre-test to 17.79 at post-test. The mean N-gain score of 0.70 indicated a moderate level of improvement, and the paired-samples t-test revealed a statistically significant difference between the two measurements (p < 0.001). Sub-indicator analysis further showed that improvement in the moral domain was stronger than in the religious domain. These findings suggest that a structured sequence of observing, asking, trying, reasoning, and communicating can provide a meaningful pedagogical pathway for values-oriented learning in early childhood education. Although the evidence is context-bound, the study contributes to wider global discussions on how inquiry-oriented pedagogy can be extended beyond cognitive learning to support moral and religious development in culturally and religiously plural early childhood settings across diverse educational contexts worldwide today.